Running Propensities of Athletes with Hamstring Injuries - Dai Sugimoto; Brian D. Kelly; David L. Mandel; Duncan A. d'Hemecourt; Sara C. Carpenito; Charles A. d'Hemecourt; Pierre A. d'Hemecourt (MDPI AG, 2019)
The current study aims to compare the mechanical propensities between healthy runners and runners with hamstring injuries. Retrospective case-control video analysis was used. A total of 35 (12 male and 23 female) videos of runners with hamstring injuries were compared with videos of sex-, age-, mass-, and height-matched healthy control runners. The main outcome variables were trunk posture angles, overstride angles, and foot strike patterns. An independent t-test and chi-squared tests were employed to analyze the main outcome variables between the runners with hamstring injuries and the healthy control runners. The statistical significance of less than 0.05 (p < 0.05) was used. The runners with hamstring injuries had a 1.6° less forward-trunk posture angles compared with the healthy control runners (p = 0.043). Also, the runners with hamstring injuries demonstrated a 4.9° greater overstride angles compared with the healthy control runners (p = 0.001). Finally, the runners with hamstring injuries had a tendency of rearfoot strike, while the healthy control runners showed a forefoot strike pattern (p = 0.004). In conclusion, the runners with hamstring injuries demonstrated different running mechanical propensities compared with the healthy runners.